2016
DOI: 10.1088/1755-1315/49/7/072014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dynamic behavior of turbine runner blades during transients using indirect measurements

Abstract: Abstract. Turbine start-up transients are induced by the wicket gates opening sequence and generate high amplitude stress cycles. These stress cycles have a detrimental effect leading to faster crack growth in the runner blades. Using a series of direct measurements taken on a prototype runner in order to find the optimal start-up parameters exposes both the runner and the instrumentation to a series of successive damaging transient events during the optimization process. To solve this, finding sensors strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…These methods consist of simplifying as much as possible the on-site measurements tests. Instead of using sensors on the runner, which implies much longer periods of time for the installation, the basic idea is to estimate the same information with sensors installed on the stationary frame (vibration sensors & pressure sensors) or strain gauges on the rotating shaft [68,90], whose installation can take few hours or a couple of days.…”
Section: Indirect Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods consist of simplifying as much as possible the on-site measurements tests. Instead of using sensors on the runner, which implies much longer periods of time for the installation, the basic idea is to estimate the same information with sensors installed on the stationary frame (vibration sensors & pressure sensors) or strain gauges on the rotating shaft [68,90], whose installation can take few hours or a couple of days.…”
Section: Indirect Methodsmentioning
confidence: 99%
“…Diagne et al [90] used shaft torsion measurement for this purpose. According to that study, shaft-torsion measurements are highly correlated to stress on the runner and this type of measurements are much cheaper (usually strain gauges on the shaft can be placed in one day without dewatering the runner).…”
Section: Indirect Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, there is direct measurement [5] during dedicated measurement campaigns, often done during unit commissioning. Then, there is indirect measurement [6], which is more suitable for online monitoring since one of the main limitations of direct measurement relates to the feasibility of permanent instrumentation of runner blades with strain gauges. Currently, strain gauges are laborious to install, have a limited life expectancy and become highly expensive as more detailed spatial information is required.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study on a 444 MW prototype Francis turbine suggested that the accelerometers located in the turbine guide vane, bearing, head cover, and in the shaft captured more phenomena compared to other sensors installed in other locations of the turbine [ 15 ]. Strain measurements on the shaft of a propeller turbine during start-up operations showed that torsion measurement can be correlated to the strain measured on the blade hotspot and be used for turbine start-up optimization [ 16 ]. Another experimental investigation on a 200 MW prototype Francis turbine showed that shaft oscillation at the lower guide bearings increased at a part load operation when the pressure fluctuations were intense in the draft tube [ 17 ].…”
Section: Introductionmentioning
confidence: 99%